The Significance of Contractual Intention: A Comparative Analysis on English and Indonesian Law - Ulya Yasmine Prisandani (Fakultas Hukum Universitas Islam Indonesia, 2018)
The legal terms of a contract vary from one country to another, and the will in a contract often influences whether a contract has been perfectly established. Establishing a contract between parties from different legal systems has the risk of defect and imperfection in the establishment of the contract, which can influence the rights of one party when a contract related dispute occurs. The British law requires supply, acceptance, and reciprocity as legal conditions for contracts, but the legal terms of a contract in Indonesian law are stipulated in the Civil Code. Therefore, this study aims to develop a comparative analysis relating to the role of contractual will in determining the validity of a contract in British and Indonesian laws as well as their method in interpreting contracts. The study used the normative qualitative method with a comparative approach to the two legal systems completed with a description of the will in a contract based on CISG. Both legal jurisdictions are open for the possibility of assuming will incompatibility in a contract as 'oversight', and in such cases, a contract can deem void.